2007
DOI: 10.1088/0953-8984/19/13/136204
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature thermal expansion and structural behaviour of stromeyerite, AgCuS

Abstract: Results of simultaneous thermal analysis, synchrotron and neutron powder diffraction in the range from room temperature up to the melting point at 936 K on non-superionic orthorhombic β-AgCuS as well as on superionic hexagonal α-and cubic δ-AgCuS are reported. On heating the sample is only stable in argon. The following phase transitions occur in AgCuS at elevated temperatures:The volume changes at the superionic β −→ α and α −→ δ phase transitions are about 2.3 and 0.6%. The volume thermal expansion coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 25 publications
4
41
1
Order By: Relevance
“…Taking this into account, we suggest a correlation between the results of the electrochemical measurements from Kadrgulov et al [3], which revealed only a relatively modest increase in the ionic conductivity with temperature within fcc-(Ag x Cu 1-x ) 2 S, and our diffraction results, which show no pronounced cation redistribution. The same correlation was supposed for related superionic fcc-AgCuSe [19], fcc-AgCuS [21] and fcc-(AgI) x -(PbI 2 ) 1-x with x= 5 4 and 3 2 [17]. Doubtless, single crystal measurements of superionic bcc-and fcc-Ag 3 CuS 2 would provide more information about the underlying structure.…”
Section: Bcc-ag 3 Cusmentioning
confidence: 58%
See 1 more Smart Citation
“…Taking this into account, we suggest a correlation between the results of the electrochemical measurements from Kadrgulov et al [3], which revealed only a relatively modest increase in the ionic conductivity with temperature within fcc-(Ag x Cu 1-x ) 2 S, and our diffraction results, which show no pronounced cation redistribution. The same correlation was supposed for related superionic fcc-AgCuSe [19], fcc-AgCuS [21] and fcc-(AgI) x -(PbI 2 ) 1-x with x= 5 4 and 3 2 [17]. Doubtless, single crystal measurements of superionic bcc-and fcc-Ag 3 CuS 2 would provide more information about the underlying structure.…”
Section: Bcc-ag 3 Cusmentioning
confidence: 58%
“…This model yields the following temperature dependence for the parameters of the average structure of fcc-Ag 3 CuS 2 : the temperature factors for the cations and anions practically do not change with temperature and there are no pronounced changes in the temperature dependence of the cation occupancies. Note that diffraction results on a number of copper and silver based chalcogenides and halides (for instance, results of [17][18][19][20][21]) imply that the ionic conductivity can be sensitive to details of the cation redistribution between available interstitial sites versus temperature as well as to the stoichiometry of the material. Taking this into account, we suggest a correlation between the results of the electrochemical measurements from Kadrgulov et al [3], which revealed only a relatively modest increase in the ionic conductivity with temperature within fcc-(Ag x Cu 1-x ) 2 S, and our diffraction results, which show no pronounced cation redistribution.…”
Section: Bcc-ag 3 Cusmentioning
confidence: 99%
“…The silver copper sulfides have been examined historically for their ionic conductivity at high temperatures, and a number of studies have examined their phase behaviour. 31 , 32 The most recent structural studies on the room temperature phases of these two compounds have been performed by Baker et al 33 , 34 and Trots et al 35 , 36 using single crystal X-ray and neutron powder diffraction. Previous theoretical investigations of AgCuS have focused on its high temperature cubic phase 37 and its behaviour under pressure; 38 the most recent work, however, showed that it exhibits p-type conductivity with a significant thermopower (∼665 μV K –1 ) at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In order to explain correlations between high-ionic conductivity and crystal structure in AgCuSe and AgCuS, measurements between room temperature and 723 K have been carried out. The data were analyzed by a whole-pattern decomposition procedure and Rietveld refinement with fixed values of already refined parameters [12]. In a small (150 μg) Martian meteorite sample, it was possible to deduce the cation distribution within two pyroxene phases: pigeonite and augite.…”
Section: Volume 18 • Number 4 • 2007mentioning
confidence: 99%